2015
DOI: 10.5194/se-6-799-2015
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation in karst terrain of southwestern China allocates more biomass to roots

Abstract: Abstract. In mountainous areas of southwestern China, especially Guizhou province, continuous, broadly distributed karst landscapes with harsh and fragile habitats often lead to land degradation. Research indicates that vegetation located in karst terrains has low aboveground biomass and land degradation that reduces vegetation biomass, but belowground biomass measurements are rarely reported. Using the soil pit method, we investigated the root biomass of karst vegetation in five land cover types: grassland, g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 29 publications
5
70
1
1
Order By: Relevance
“…The reason for the decrease in soil erosion rates as a consequence of vegetation recovery is because the vegetation reduces or avoids the rainfall erosivity (Cerdà, 1998;Keesstra, 2007;Ni et al, 2015;Taguas et al, 2015), improves soil properties and reduces runoff and soil losses. Keesstra et al (2009) found that vegetation recovery reduced sediment losses in Slovenia.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the decrease in soil erosion rates as a consequence of vegetation recovery is because the vegetation reduces or avoids the rainfall erosivity (Cerdà, 1998;Keesstra, 2007;Ni et al, 2015;Taguas et al, 2015), improves soil properties and reduces runoff and soil losses. Keesstra et al (2009) found that vegetation recovery reduced sediment losses in Slovenia.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the AGB of this old-growth karst forest was significantly lower than that of other typical evergreen broad-leaved forests at similar latitudes (Yang and Cheng 1991;Zhu et al 1995;Yu et al 2002). Belowground biomass of different vegetation restoration stages at the same site has also been estimated using specific sampling method of digging four soil pits around an averaged sample tree (Luo et al 2010), as well as through normal soil pit method with 10 soil pits in a plot (Ni et al 2015). These sampling methods revealed higher BGB and root-shoot ratio of the karst forest than that of typical evergreen broad-leaved forests in subtropical China.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cover % of CB and CS were almost the same (Table 1.3). Therefore, the larger size of stems and root systems of the different species of spontaneous vegetation had a decisive effect on reducing the runoff and nitrate loss, as found by other authors recently (Ni et al, 2015;Ola et al, 2015;Shaw et al, 2016).…”
Section: Discussionsupporting
confidence: 54%